Tindak Tutur Direktif dalam Film â€œKeluarga Cemaraâ€ Karya Gina S. Noer sebagai Alternatif Bahan Ajar Teks Drama Kelas XI SMA - Miftakhur Rohmah; Arisul Ulumuddin; Azzah Nayla (Universitas PGRI Semarang, 2023)
Â Â Â Â Â Â Â Â Â Â Â Â Â The purpose of this study is to describe the form of directive speech in the film â€œKeluarga Cemaraâ€ by Gina S. Noer and to describe the film â€œKeluarga Cemaraâ€ by Gin S. Noer as an alternative material for teaching drama texts in high school. The method used in this research is a qualitative research with a descriptive approach. Qualitative research is research that has the aim of describing and analyzing or revealing and revealing. The data collection technique in this study used the listening method and the note-taking technique. The results of research on the film